Field notes contributed by Richard Jule Holllis with verifying documentation, fall 1981 - Hollis, Richard Juleet al (1981)
Field notes were contributed by Richard Jule Hollis and other observers. Verifying documentation of an extraordinary sighting of a Goshawk is included. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1981. Epson - sheet feed